Nesting interactions of the social wasp Dolichovespula saxonica [F.] (Hymenoptera: Vespinae) in wooden nest boxes for birds in the forest reserve „Las Piwnicki” in the Chełmno Land (Northern Poland) - Pawlikowski, Tadeusz; Pawlikowski, Krzysztof (Ecological Questions, 2010)
The aim of this research was to investigate the process of colonization in wooden nest boxes for birds by the wasp Dolichovespula saxonica [F.] in the forest reserve “Las Piwnicki” during 1986-1987. About 69% of 150 nest boxes were colonized (36% by D. saxonica) in 1986 and 35% (10% by D. saxonica) in 1987. Parasite Shecophaga vesparum Court was observed inside small cell nests (SC) and large cell nests (LC) in the ratio of 5(SC) : 3(LC). During the two seasons, the decrease in the number of parasited nests followed with the ratio of 10(1986) : 1(1987). Competition of the „wasp - wasp” type (VV) compared to other competition types, such as „wasp - bird” (VA) and different types with wasps (DT), was the most frequent one among the interactions and followed with the ratio 1(VV) : 7(VA) : 5(DT). The number and proportions of construction types of nests during the studied growing seasons seem to prove the regular and irregular development of the Dolichovespula saxonica colony.